Índice preditor de reserva ovariana (ORPI) para controle de estimulação ovariana individualizado - Oliveira, Joao Batista A. [UNESP]; Petersen, Claudia G. [UNESP]; Mauri, Ana L.; Cavagna, Mario; Baruffi, Ricardo L R.; Franco Junior, Jose Gonçalves [UNESP] (My University, 2013)
Objective: to expand the evaluation of a new ovarian response prediction index (ORPI), which was based on the AMH, AFC and age, and to verify its reability as a predictor of ovarian response to stimulation in assisted reproductive technology (ART) cycles. Methods: A total of 129 patients enrolled in the ICSI programme were included. The ORPI values were calculated by multiplying the AMH level (ng/ml) by the number of antral follicles (2-9 mm), and the result was divided by the age (years) of the patient (ORPI=(AMH × AFC)/Patient age). Results: Spearman's test revealed significant correlations (P<0.0001) between the ORPI and the number of oocytes collected and the number of follicles. Logistic regression revealed that ORPI values were significantly associated with the likelihood of collecting ≥4 oocytes (OR=45.56), ≥4 MII oocytes (OR=6.01) and ≥15 oocytes (OR=6.15; P<0.0001). Based on the ROC curves, the ORPI accurately predicted a low ovarian response (<4 oocytes retrieved; area under the curve (AUC):0.91), collection of ≥4 MII oocytes (AUC:0.85) and an excessive ovarian response (≥15 oocytes retrieved; AUC:0.89). Conclusions: The ORPI exhibited an excellent ability to predict a low ovarian response and a good ability to predict a collection of ≥ 4 MII oocytes, an excessive ovarian response. The ORPI might be used to improve the cost-benefit ratio of ovarian stimulation regimens by guiding the selection of medications and by modulating the doses and regimens according to the actual needs of the patients. © Todos os direitos reservados a SBRA - Sociedade Brasileira de Reprodução Assistida.
Expand evaluation of the ovarian response prediction index (ORPI) for individualised controlled ovarian stimulation
Keywords: Age; Anti-Mullerian hormone; Antral follicles; Individualized controlled ovarian stimulation; Ovarian response prediction index; cetrorelix; chorionic gonadotropin; leuprorelin; luteinizing hormone; Muellerian inhibiting factor; recombinant follitropin; adult; age; cost benefit analysis; drug dose increase; female; human; major clinical study; named inventories, questionnaires and rating scales; oocyte; ovarian response prediction index; ovary follicle; ovary function; transvaginal echography